Karakteristik Pasien Multidrug Resistant Tuberculosis (MDR-TB) di RSUD Makassar - Nur Arifah; Tintin Sukartini; Harmayetty Harmayetty (Jurnal Penelitian Kesehatan SUARA FORIKES, 2019)
The case of multidrug resistant tuberculosis (MDR-TB) has become a threat to world health security. MDR / RR-TB causes 230,000 deaths in 2017 and most cases and deaths occur in Asia including Indonesia. MDR-TB cases that fail or are lost to treatment are one of the problems controlling MDR-TB because they can be a source of spread of treatment-resistant Mycobacterium Tuberculosis. This study aims to describe the characteristics of MDR-TB patients undergoing treatment at Makassar Hospital. This study uses qualitative studies with a phenomenological approach. The participants in this study were 18 people using purposive sampling. The study was conducted in February until April 2019. The results of this research show that there are no gender differences and productive age is more at risk of MDR-TB. Low education levels do not guarantee the risk of transmission of MDR-TB depends on the willingness to be able to obtain health information such as the internet or conventional information (leaflets or health education). The duration of treatment makes participants unable to work because they have to focus on routine treatment every day for up to 18-20 months. Families living with patients have a greater risk of contracting but are a source of patient support for completing treatment. description of patient characteristics can be a source of data to find out groups at risk of infection so that they can develop MDR-TB prevention interventions that are right on target. Keywords: characteristics; multidrug tuberculosis; qualitative. ABSTRAK Kasus MDR-TB menjadi ancaman keamanan kesehatan dunia. MDR/RR-TB menyebabkan 230.000 kasus kematian 2017 dan sebagian besar kasus dan kematian terjadi di Asia termasuk Indonesia. Kasus MDR-TB yang gagal atau mangkir dari pengobatan menjadi salah satu masalah pengendalian MDR-TB karena dapat menjadi sumber penyebaran Mycobacterium Tuberculosis yang resisten terhadap pengobatan. Penelitian ini bertujuan untuk mendekripsikan karakteristik pasien MDR TB yang sedang menjalani pengobatan di RSUD Makassar. Penelitian ini menggunakan studi kualitatif deskriptif. Partisipan dalam penelitian ini sebanyak 18 orang dengan menggunakan purposive sampling. Penelitian dilakukan pada februari hingga april 2019. Hasil penelitioan ini menunjukkan bahwa tidak adaperbedaan jenis kelamin sedangkan partisipan usia produktif lebih beresiko MDR-TB. Tingkat pendidikan rendah tidak menjamin resiko penularan MDR-TB tergantung kemauan untuk dapat memperoleh informasi kesehatan seperti internet ataupun informasi konvensional (leaflet atau penyuluhan kesehatan). Lamanya pengobatan membuat partisipan tidak dapat bekerja karena harus fokus dengan pengobatan rutin setiap hari hingga 18-20 bulan. Keluarga yang tinggal bersama penderita memiliki resiko yang lebih besar untuk tertular tetapi menjadi sumber dukungan pasien untuk dapat menyelesaikan pengobatan. gambaran karakteristik pasien dapat menjadi sumber data untuk mengetahui kelompok beresiko terinfeksi sehingga dapat mengembangkan intervensi pencegahan kejadian MDR-TB yang tepat sasaran Kata kunci: karakteristik; multidrug resistant tuberculosis; kualitatif.